1997
DOI: 10.1073/pnas.94.17.9000
|View full text |Cite
|
Sign up to set email alerts
|

Two-component kinase-like activity of nm23 correlates with its motility-suppressing activity

Abstract: Nm23 genes, which encode nucleoside diphosphate kinases, have been implicated in suppressing tumor metastasis. The motility of human breast carcinoma cells can be suppressed by transfection with wild-type nm23-H1, but not by transfections with two nm23-H1 mutants, nm23-H1 S12OG and nm23-H1 P96S . Here we report that nm23-H1 can transfer a phosphate from its catalytic histidine to aspartate or glutamate residues on 43-kDa membrane proteins. One of the 43-kDa membrane proteins was not phosphorylated by either nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
112
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 34 publications
1
112
0
1
Order By: Relevance
“…In humans, there are eight members of the Nm23 family (Nm23-H1-8, respectively), and in addition to their nucleoside diphosphate kinase activity, members of this family have both histidine protein kinase and phosphotransferase activities (Wagner et al, 1997;Lacombe et al, 2000;Steeg et al, 2008). Nm23-H1, which has DNase activity (Fan et al, 2003), is primarily cytoplasmic, whereas Nm23-H2 is both nuclear and cytoplasmic, and binds DNA (Postel et al, 2000;Bosnar et al, 2004Bosnar et al, , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, there are eight members of the Nm23 family (Nm23-H1-8, respectively), and in addition to their nucleoside diphosphate kinase activity, members of this family have both histidine protein kinase and phosphotransferase activities (Wagner et al, 1997;Lacombe et al, 2000;Steeg et al, 2008). Nm23-H1, which has DNase activity (Fan et al, 2003), is primarily cytoplasmic, whereas Nm23-H2 is both nuclear and cytoplasmic, and binds DNA (Postel et al, 2000;Bosnar et al, 2004Bosnar et al, , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the NDPK activity alone cannot explain these pleomorphic effects. The nm23 proteins have been reported to possess both a histidine protein kinase activity and a phosphotransferase activity; the latter potentially represents an additional mechanism by which the nm23s can influence the metastasis and differentiation processes (MacDonald et al, 1996;Wagner et al, 1997). To date, several nm23 interactors have been described in mammals, including Rad, Tiam1, Arf6, the nucleosome assembly protein SET, Cdc42, EBNA1 and KSR (Otsuki et al, 2001;Tseng et al, 2001;Palacios et al, 2002), although their roles are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown that these mutants retain: (1) the catalytic activity; (2) the ability to autophosphorylate His118 (see Figure 4b); (3) the phospho-Histidine-dependent Serine autophosphorylation; (4) the ability to transfer phosphate from His118 to ATP-citrate lyase and succinic thiokinase His residues; and (5) the ability to bind DNA (tested only for nm23-H2 P96S) MacDonald et al, 1993;Postel et al, 1996;Wagner et al, 1997). On the contrary, the P96 and S120 residues are essential for the motility suppressing e ect and the`phosphorelay system' from Histidine residue to Aspartate and/or Glutamate residues of nm23-H1 (Hartsough and Steeg, 1998;MacDonald et al, 1996;Wagner et al, 1997). In this regard, our results provide the ®rst evidence that mutations of residues P96 and S120 a ect in di erent ways NDPK protein function.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that di erent NDPK oligomer species are involved in a variety of cellular processes where enzymatic activity is required (Engel et al, 1998;Hartsough and Steeg, 1998;Mesnildrey et al, 1998;Wagner et al, 1997). Elucidation of the role of the biological interactions between PRUNE and nm23-H1 would be a major step towards understanding the role of NDPKs in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation